Rancang Bangun Mesin Pencetak Pakan Ikan Menggunakan Metode VDI 2221 - rae, matias; Mangesa, Duad Pulo; Tarigan, Ben V. (Universitas Nusa Cendana, 2022)
ABSTRACT A reality for today's business world, that many small and medium industries and households are trying to build themselves to meet the growing need for fish feed. Based on this, it is appropriate that the production equipment owned must be optimized to support the effectiveness and efficiency of the fish feed production process. The VDI 2221 method uses a systematic approach to design for engineering systems and engineering products. This VDI 2221 method makes it easier for designers to make a product so that product design can be achieved. The author has a design to make a fish feed printing machine in the hope that it can be used as an alternative to produce products faster and more efficiently. The results of the design using the VDI 2221 method of fish feed printing machine are, using a motor power of 1 HP = 750 watts with a tool capacity of 42 kg/hour. Keywords: design, VDI 2221 method, feed printing device.